An Examination of Government Policies for E-Learning in New Zealand’s Secondary Schools - Allison Powell; Michael Barbour (Journal of Open, Flexible and Distance Learning, 2011)
In 2006 the North American Council for Online Learning surveyed the activity and policy relating to primary and secondary e-learning, which they defined as online learning, in a selection of countries. They found most were embracing e-learning delivery of education as a central strategy for enabling reform, modernising schools, and increasing access to high-quality education. While North American countries appeared to be using the internet as a medium to provide distance education at the secondary level longer than most countries, the lack of a guiding vision has created uneven opportunities for students depending on which state or province they live in. In New Zealand, the government has sought to provide a vision or guiding framework for the development of e-learning. In this article we trace that vision by describing three policy documents released by the New Zealand government over the past decade, and how that vision for e-learning has allowed increased development of primary and secondary online learning.